EDUCATIONAL GAME DESIGN ASA 5S CONCEPT LEARNING TOOL AT PT. XYZ - Fandy Neta; Ferdiansyah Himawan; Muhammad Nashrullah; Mira Chandra Kirana (Jurnal Ilmu Komunikasi, 2020)
The educational game is very interesting to develop because it has several advantages. Currently educational games can also be applied to companies that want to provide learning to employees in an interactive and different way, one of them is PT XYZ. 5S is a Japanese term that consists of Seiri, Seiton, Seisho, Seiketu, and Shitsuke. 5S was chosen as the topic of the game because it is a guideline for employees to create order, cleanliness, and safety, therefore the learning process requires its own challenges. Applications are built using the Multimedia Development Life Cycle method, which consists of six stages, namely concept, design, material collection, assembly, testing, and implementation. Alpha testing, testing the functionality of the application using the Blackbox testing method with the results of each application function running. Beta testing, testing of the Expert Test and Employee Sample Test to measure the level of effectiveness of the game as a learning medium at PT XYZ, provides excellent results on game effectiveness, namely: 5S 90% Material Expert Test Test Percentage, 90% Game Expert Test, and Sample Test Employees 94.66% all three are at very good intervals.